European Sexual Citizenship : Human Rights, Bodies and Identities - Ammaturo, Francesca Romana (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is an innovative and critical contribution to the study of the human rights of lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ) people in the context of Europe. Combining legal and Foucauldian approaches, it investigates the ways in which current discourses about LGBTIQ rights in Europe are tightly bound to contemporary debates about national and trans-national citizenship. The author defines and analyzes the concept of 'multisexual citizenship' to illustrate new, flexible forms of sexual and gendered citizenship that could radically transform practices of citizenship and the current human rights framework in Europe. She does this by combining critical deconstructions of the case law of the European Court of Human Rights with ethnographic observations and sociological analysis. This interdisciplinary work will appeal to sociologists, lawyers and researchers of gender and LGBTIQ rights. Francesca Romana Ammaturo is Lecturer in Sociology and Human Rights at the University of Roehampton, UK. Her research focuses on the rights of lesbian, gay, bisexual, trans and intersex people in Europe.
Keywords: Social sciences.; Human rights.; Social structure.; Social inequality.; Sociology.; Human body -- Social aspects.; Social justice.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books